Layout Furniture in Supporting the Visually Impaired People at the Dining Area of PSBN Wyata Guna - Wasilah, Deanawati Insani; Amalia, Friska (Indonesian Journal of Visual Culture, Design, and Cinema, 2023)
The dining room at PSBN Wyata Guna is used for visually impaired people when it's time to eat in the dining room. This room has high potential complexity and level of activity. Because of the activities that occur, the movement of visually impaired persons is essential in this dining room. But the lack of treatment in the dining room causes frequent collisions and difficulties for the visually impaired person in finding directions. Therefore, we need a stimulus that can support the movement of the visually impaired person in circulation. Through previous research, stimuli that play a high role are sound and layout. This study uses an experimental method to determine how significant the layout and sound stimuli are for visual impaired person in circulation. And it has been concluded that distance is not significant to determine the time of movement in circulation in the dining room, the most important thing for people with visual impaired person is the instructions located in the area of circulation and sound stimuli which are located at critical points. The instructions referred to can be in the form of furniture or other objects if they do not inhibit circulating movements and have a consistent distance, while sound is needed to convince persons with disabilities that their direction is correct. Furthermore, this research can be a recommendation for further research, both academics and related institutions as well as input for interior designers and architects in designing dining rooms for persons with disabilities on a small scale.